2004
DOI: 10.1164/rccm.200302-165oc
|View full text |Cite
|
Sign up to set email alerts
|

Association of Minimal Rejection in Lung Transplant Recipients with Obliterative Bronchiolitis

Abstract: The clinical significance of minimal acute rejection (grade A1) in lung transplant recipients is unknown. We prospectively analyzed 1,159 transbronchial lung biopsies in 184 patients. Two hundred seventy-nine biopsies in 128 participants confirmed A1 histology at a mean postoperative day of 229 +/- 340. Sixty four of 255 surveillance A1 lesions progressed to high-grade acute rejection by 3 months of follow-up, whereas 40 developed new lymphocytic bronchiolitis. Twenty-four A1 biopsies were symptomatic, with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 13 publications
6
105
1
4
Order By: Relevance
“…HOPKINS et al [41] have reported that grade A1 acute cellular rejection remains relatively prevalent on surveillance transbronchial biopsies up to 2 years post-transplant. Available studies suggest that patients with multiple episodes of Grade A1 rejection have an earlier onset of BOS, and a single episode of A1 rejection was found to be independently associated with progression to BOS [42].…”
Section: Minimal (Grade A1) Acute Cellular Rejectionmentioning
confidence: 99%
“…HOPKINS et al [41] have reported that grade A1 acute cellular rejection remains relatively prevalent on surveillance transbronchial biopsies up to 2 years post-transplant. Available studies suggest that patients with multiple episodes of Grade A1 rejection have an earlier onset of BOS, and a single episode of A1 rejection was found to be independently associated with progression to BOS [42].…”
Section: Minimal (Grade A1) Acute Cellular Rejectionmentioning
confidence: 99%
“…Значение минималь ного ОКО (стадия IА) неоднозначно. P.M.Hopkins et al [41] показано, что ОКО стадии IА преобладает в плановых трансбронхиальных биоптатах в течение первых 2 лет после трансплантации. По результатам других опубликованных исследований установле но, что у больных с многочисленными эпизодами отторжения стадии 1А СОБ развивается раньше, и каждый эпизод отторжения стадии IА связан с про грессированием СОБ независимо от других призна ков [42].…”
Section: рекомендацияunclassified
“…При поиске литературы для данных рекоменда ций были обнаружены 2 наблюдательных исследова ния, в которых отмечено, что при усиленной имму носупрессии и минимальном ОКО (стадия IА) может снизиться риск развития СОБ [41,43]. В ис следовании [43] при использовании внутривенных ГКС с последующим курсом пероральных ГКС в снижающейся дозе СОБ не развивался (р = 0,48), тогда как отсутствие лечения системными ГКС было четко связано с развитием СОБ (р = 0,01).…”
Section: рекомендацияunclassified
See 2 more Smart Citations